PEMANFAATAN DATA CITRA SATELIT SENTINEL-1 UNTUK PEMANTAUAN SEBARAN TUMPAHAN MINYAK DI WPP 713 - Komang Iwan Suniada (Pusat Riset Kelautan, 2021)
The Makassar Strait which is a part of the Fisheries Management Area (WPP) 713 and the Indonesian Archipelago Sea Channel (ALKI) II is an economic route that connects the Pacific Ocean in north and Indian Ocean at south through the middle of Indonesia archipelago. The high traffic on this route creates risks to national security, illegal fishing, and environmental pollution due to oil spills. One method that can be used to monitor oil spills in open water is remote sensing satellite with SAR (Synthetic Aperture Radar) data. The satellite data used in this study is a SAR image from the Sentinel-1 satellite. The advantage of radar satellites is their ability to perform data acquisition during the day or night and in all weather conditions. The method used to detect oil spills is an automatic method found in the SNAP software, while the length and area of the oil spill are calculated using the spatial analysis method which is available in the QGIS software. The results of this study in the Makassar Strait found that there was an oil spill with a length of about 11.7 km and an area of about 22.8 km². The oil spills in this study resemble the characteristics of an oil spill caused by a moving ship. This incident indicating the violation is suspected to have occurred in the area. Utilization of Sentinel-1 SAR data to monitor illegal oil spills is expected to reduce violations that occur in Indonesian territorial waters.